The Effect of Oral Pancreatic Enzyme Supplementation on the Course and Outcome of Acute Pancreatitis: A Randomized, Double-Blind Parallel-Group Study - Kahl, Stefan; Schütte, Kerstin; Glasbrenner, Bernhard; Mayerle, Julia; Simon, Peter; Henniges, Friederike; Sander-Struckmeier, Suntje; Lerch, Marcus M; Malfertheiner, Peter (JOP. Journal of the Pancreas, 2014)
Context Pancreatic exocrine insufficiency is a significant problem after acute pancreatitis. Objective To evaluate whether oral pancreatic enzyme supplementation improves the recovery of pancreatic exocrine function and to explore the efficacy, safety and tolerability of pancreatic enzyme supplementation in patients during the refeeding period after acute pancreatitis. Design Prospective double-blind, placebo controlled, randomized study. Patients The sudy included 56 patients with acute pancreatitis. Main outcome measures Primary efficacy variable was recovery from pancreatic exocrine insufficiency. Secondary objectives were body weight, abdominal pain, course of APACHE II score, patient’s symptoms and quality of life. Results Twenty of the 56 patients showed low fecal elastase values indicating pancreatic exocrine insufficiency after acute pancreatitis. Median time to recovery from exocrine pancreatic insufficiency was 14 days in the enzyme supplementation group and 23 days in the placebo group but overall differences for primary and all but one secondary endpoint did not reach statistical significance. However, a positive tendency in favour of enzyme supplementation was found for quality of life parameters (FACT-Pa) in all subscores. There were no relevant differences between placebo and oral pancreatic enzyme supplementation detected with respect to safety and tolerability. Conclusion Enzyme supplementation positively effects the course of acute pancreatitis if administered during the early refeeding phase after acute pancreatitis. There is evidence that oral pancreatic enzyme supplementation has a positive impact on the course of the disease and the global health status (less weight loss, less flatulence, improved quality of life). Oral pancreatic enzyme supplementation was safely administered and can be added to the treatment regimen of patients in a refeeding status after severe acute pancreatitis. Image: Kaplan-Meier estimates of the proportion of subjects with a response (Figure 2)